2019
DOI: 10.1101/gr.233288.117
|View full text |Cite
|
Sign up to set email alerts
|

4q-D4Z4 chromatin architecture regulates the transcription of muscle atrophic genes in facioscapulohumeral muscular dystrophy

Abstract: Despite increasing insights in genome structure organization, the role of DNA repetitive elements, accounting for more than two thirds of the human genome, remains elusive. Facioscapulohumeral muscular dystrophy (FSHD) is associated with deletion of D4Z4 repeat array below 11 units at 4q35.2. It is known that the deletion alters chromatin structure in cis, leading to gene up-regulation. Here we show a genome-wide role of 4q-D4Z4 array in modulating gene expression via 3D nuclear contacts. We have developed an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 95 publications
1
16
0
Order By: Relevance
“…We developed an algorithm, implemented in MATLAB, in order to automatically analyze 3D RNA FISH and PML proteins in fluorescence cell image z ‐stacks. The algorithm is derived from Cortesi et al () with some adaptations. It performs the 2D segmentation of cell nuclei and the detection of FISH and PML spots for each slice of the stack followed by the 3D reconstruction and identification of nuclei and spots.…”
Section: Methodsmentioning
confidence: 99%
“…We developed an algorithm, implemented in MATLAB, in order to automatically analyze 3D RNA FISH and PML proteins in fluorescence cell image z ‐stacks. The algorithm is derived from Cortesi et al () with some adaptations. It performs the 2D segmentation of cell nuclei and the detection of FISH and PML spots for each slice of the stack followed by the 3D reconstruction and identification of nuclei and spots.…”
Section: Methodsmentioning
confidence: 99%
“…While we previously demonstrated that carefully controlled mitochondrial ROS signaling is essential for muscle membrane repair, chronic oxidative stress (8-24 h) interferes with this process [28,29]. Additionally, recent chromosomal conformation capture and proteomic analyses revealed upregulation of membrane trafficking pathways (endocytosis and exocytosis) in FSHD myoblasts, suggesting that there may be imbalances in essential membrane repair pathways in FSHD [30,31].…”
Section: Introductionmentioning
confidence: 93%
“…Facioscapulohumeral muscular dystrophy (FSHD) is an autosomal dominant neuromuscular disorder characterized by asymmetric muscle weakness, atrophy, fatty infiltration, and inflammation, typically beginning in the muscles of the face and periscapular region and progressing to the lower extremities over time [1]. In~95% of cases, disease onset is linked to a contraction in the number of 3.3 Kb, GC-rich D4Z4 repeats on chromosome 4q35 from 11-100 (average [25][26][27][28][29][30][31][32][33][34][35] in healthy individuals, to 1-11 repeats in FSHD1 [2,3]. This contraction leads to a loss of repressive histone marks, relaxation of chromatin, and DNA hypomethylation, which reverses the normal pattern of epigenetic repression of the D4Z4 locus and facilitates abnormal gene expression [3].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility to use the percentage values of methylated CpGs at D4Z4 as a diagnostic marker for FSHD is further weakened by the fact that DNA methylation could not be considered per se. It is now well established that DNA methylation is only one among numerous indicators of chromatin structure at D4Z4 and several research groups reported that alterations of chromatin structure is reflected by post-translational histone modifications [48,[98][99][100], by the binding of various non-histone proteins and RNAs on the repeat array [39,43,101], and by higher order chromatin structures formation [102][103][104].…”
Section: Trans-acting Factorsmentioning
confidence: 99%
“…Since CTCF has also been shown to mediate chromatin loop formation and to generate TADs (topologically associated domain) [108][109][110][111] the increased CTCF binding to D4Z4 in FSHD may result in altered nuclear and chromatin organization. In particular, using an integrated genome wide approach (4C-seq) it has been reported that 4q-D4Z4 interactome is altered in FSHD1, leading to a chromatin switch toward an active state (mediated by enhancer-promoter interactions), which in turn results in the transcriptional activation of genes involved in muscular atrophy [103].…”
Section: Trans-acting Factorsmentioning
confidence: 99%